Relationship between Employee Development and Work Motivation of Solider Rural Bank Employees - Rusmia Maria Situmorang (Institute of Computer Science (IOCS), 2019)
Solider Rural Credit Bank is a company engaged in people's credit (savings / loans). Employee development with efforts to improve skills and general knowledge for Solider Rural Credit Bank employees is a part that encourages them to work harder in the future with the desire to prepare themselves for new positions. Based on preliminary research that has been done, the problems faced by the company are as follows: